Adaptive Governance During a Crisis: The Case of Livestock Agriculture Farm Sector in the Philippines - Asoy, Rhizza Mae L.; Batara, Enrique B.; Hussien, Eucil P.; Palomares, Perla P. (Universitas Muhammadiyah Yogyakarta, 2026)
This study explores adaptive governance of the livestock agriculture sector during the simultaneous COVID-19 pandemic and animal disease outbreak crisis in the province of Bukidnon, Philippines. It investigates the challenges faced, the coping strategies employed, and the practices developed by livestock farmers in response to the crisis. Qualitative data were collected from key informant research participants through in-depth interviews with eight farmers or farm personnel from both large-scale and smallholder farms across the four different livestock sectors – pig, cattle, dairy, and poultry. Findings showed that some challenges faced by livestock farms included difficulty complying with government veterinary requirements, transportation and logistics issues, and uncertainty about the availability of farm labor. Despite these challenges, the farmers were able to employ innovations and coping strategies to continue their livestock production, such as mixed farming, in-housing, and shifting farm personnel's work, as well as implementing farm-tailored biosecurity measures. The study demonstrates that adaptive governance is a practical necessity at the ground level of any societal sector in the face of a crisis. This study is the first to delve into adaptive governance practice in Philippine livestock agriculture during the pandemic and animal disease outbreak crisis.